The Conflict Study of Various Traditional and Modern Approaches in R. K. Narayan’s Novels: The Social and Cultural Dynamics in R.K. Narayan's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
R. K. Narayan was conceived in English ruled India in the recent city of Madras later renamed Chennai in 1906 and the greater part of his works identified with the anecdotal south Indian town of Malgudi. Narayan who is frequently contrasted and William Faulkner, alike the last abides in the social settings and the typical existence of his characters with funniness and empathy and the vitality that pushes normal life as the engaging motivations. In 1933, Narayan met and experienced passionate feelings for a multiyear old young lady who lived in his neighborhood and conflicting with all prophetic guidance disliking proposed marriage proceeded to wed her and however the marriage not extensive with his significant other Rajam kicking the bucket rashly, her entrance into his life began changing occasions for him in better ways. The initial three books composed by Narayan, manage socially acknowledged wickedness hones. In R.K. Narayan the contention between the general public and the individual is more entangled and hard to fathom. Narayan, as an author of the white collar class favors but then, regrets the progressive debasement of the old estimations of life. Another age of bike riding, liquor sneaking young men focused on a get-rich-no matter what reasoning group his canvas. The essence of the tales remains either the issue of the maturing father or the grandma or the docile spouse and the arrangement they touch base at long last after much agony, mortification and self-looking isn't just individual, however curiously Indian and customary. Narayan's books delineate life in the little town called Malgudi—an image of consistently changing present day India. Malgudi is a smaller than expected India and Narayan perpetually focuses on this customary and agent town where the tenants are basically human and consequently have the kinfolk send with the changing social and political conditions of the nation. Narayan sees the new Malgudi as a field of flighty and wild powers.